2021
DOI: 10.1055/a-1486-8169
|View full text |Cite
|
Sign up to set email alerts
|

Pyridine-Mediated B–B Bond Activation of (RO)2B–B(OR)2 for Generating Borylpyridine Anions and Pyridine-Stabilized Boryl Radicals as Useful Boryl Reagents in Organic Synthesis

Abstract: Significant developments have been achieved in recent years toward the utilization of (RO)2B-B(OR)2 for exploring transition metal-free organic transformations in organic synthesis. Among the various combinations of Lewis bases with diborons developed so far, pyridine-derivatives are simple, commercially available, and cheap compounds to expand the synthetic utility of diborons by generating borylpyridine anions and pyridine-stabilized boryl radicals via the B-B bond cleavage. These borylpyridine species media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 37 publications
0
13
0
2
Order By: Relevance
“…In their pioneering work Zhu and Li showed that the B−B bond of B 2 Pin 2 could be weakened upon coordination of 4‐cyanopyridine to the boron center [28] . This coordination implied a decrease of the calculated BDE to 66.5 kcal.mol −1 , allowing a smooth thermally induced homolytic cleavage of the B−B bond by a simple heating (70 °C).…”
Section: Borylation Reactions Using Boron‐centered Radicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their pioneering work Zhu and Li showed that the B−B bond of B 2 Pin 2 could be weakened upon coordination of 4‐cyanopyridine to the boron center [28] . This coordination implied a decrease of the calculated BDE to 66.5 kcal.mol −1 , allowing a smooth thermally induced homolytic cleavage of the B−B bond by a simple heating (70 °C).…”
Section: Borylation Reactions Using Boron‐centered Radicalsmentioning
confidence: 99%
“…In their pioneering work Zhu and Li showed that the BÀ B bond of B 2 Pin 2 could be weakened upon coordination of 4cyanopyridine to the boron center. [28] This coordination implied a decrease of the calculated BDE to 66.5 kcal.mol À 1 , In this seminal work, the formation of the boryl radical was valorized in the reduction of azobenzenes. [29] This boryl radical can react on styrenes and, in the presence of a reducing agent, afford the hydroboration products.…”
mentioning
confidence: 99%
“…In this system, the addition of a catalytic amount of 4-cyanopyridine was effective, and the authors suggested that the catalyst might act as a single-electron acceptor in the homolytic cleavage of boron–boron bonds. They also demonstrated the application of this system to the catalytic reduction of azo-compounds via the radical diboration of azoarenes, and the corresponding products were obtained in good to excellent yields ( Scheme 18 ) [ 99 , 100 , 101 ].…”
Section: Boron-centered Interelement Compounds In Radical Addition Re...mentioning
confidence: 99%
“…discovered that thermo‐activation, instead of photoactivation, competently triggered the intra‐complex SET of EDA complexes, expanding the EDA complex activation chemistry [15] . This represents another efficient method for the synthesis of organoboron compounds by generating active carbon radicals through SET [7a,d,16] …”
Section: C−b(sp2) Bond Construction Via Carbon–heteroatom Bond Cleavagementioning
confidence: 99%